Analisis Metode Fuzzy Tsukamoto dan Floyd-Warshall untuk Pencarian Rute Terbaik pada Wireless Sensor Network berbasis Matlab - Rizky Septian Damanik; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
This study discusses finding the shortest route with the Fuzzy Tsukamoto algorithm in the Wireless Sensor network (WSN). The Fuzzy Tsukamoto algorithm is one of the algorithms that analyzes inputs, evaluates a number of possible paths and produces solutions. This research is intended to find out the results of data visualization in matlab, the best rute that can be produced, and the time used by this Fuzzy Tsukamoto algorithm. This research was conducted in several stages including the preparation of fuzzy, fuzzification, inference, defuzzification, and continued with the Floyd-warshall algorithm to determine the most efficient distance from nodes that have been plotted randomly on WSN. This Floyd-Warshall algorithm works by relying on weights issued by Fuzzy Tsukamoto. From this study, data from experiments with nodes 10 to 1000 were obtained against distance, time, and QOS parameters in the form of throughput, packetloss, energy, delay. Based on these parameters, coherence is obtained between the number of nodes and the time used where the more nodes, the longer the time used in the algorithm computing system will be. This is in contrast to the relationship of nodes with other parameters, namely distance and QOS, where the increase in the number of nodes does not affect the result of these parameters because the node plots on the WSN are carried out randomly and the shortest route taking is based on the smallest weight of the Fuzzy Tsukamoto algorithm. Based on the results of the study, it can be concluded that fuzzy Tsukamoto's algorithm can be well in determining the shortest route of nodes that have been plotted randomly.